The Role of Formal Education for Poverty Reduction and Development in the Digital Era: A Study of Sogakope, South Tongu District, Ghana - Senna, Richard (Qualitative and Quantitative Research Center, 2024)
Bridging the gap between poverty and advancement, formal education plays a transformative role in economic and social development in the digital era. The study explores the role of formal education in poverty reduction and community development in the South Tongu District, Sogakofe, Ghana. It examines indigenous perceptions of education’s impact on poverty reduction and the relationship between household income and children's educational achievement. The study has used a mixed methods approach. The study has collected quantitative data through Likert scale questionnaires and qualitative data from key informant interviews. With a sample size of 80, findings reveal a strong agree that formal education significantly contributes to poverty reduction, improved employment opportunities, and enhanced social and cultural development. In the digital era, access to quality education, including digital literacy and technological skills, is increasingly critical for economic mobility. Respondents acknowledged that well-educated individuals foster social cohesion and economic growth. Household income plays a decisive role in educational success, as financial constraints hinder access to quality education. In the digital era, integrating technology in education can bridge socio-economic gaps, enhance learning outcomes, and drive sustainable development. Policymakers must prioritize digital inclusion in education to break the poverty cycle and ensure long-term prosperity.The contribution of this research expands the knowledge of the relationship between education and poverty reduction. In addition, it offers practical insights for designing effective interventions and policies in local and international contexts in the era of digital education.